The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1088/1757-899x/349/1/012068
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of Indonesian Natural Zeolite into Analcime Phase under Hydrothermal Condition

Abstract: Abstract. Natural zeolite is abundantly available in Indonesia and well distributed especially in the volcano area like Java, Sumatera, and Sulawesi. So far, natural zeolite from Klaten, Central Java is one of the most interesting zeolites has been widely studied. This research aims to know the effect of seed-assisted synthesis under a hydrothermal condition at 120 °C for 24 hours of Klaten's zeolite toward the structural change and phase transformation of the original structure. According to XRD and XRF analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In addition, the type of mineralization agent also has a great influence on the quality and growth rate of the crystal. Studies have shown that the use of acids, such as HCl, H 2 SO 4 , H 3 PO 4 , HNO 3 , and HCOOH, as mineralizers can reduce the crystal growth temperature to below 300 °C, thus allowing the use of relatively simpler autoclaves [51,52]. Tani et al [53] summarized the effect of mineralizers on ZrO 2 crystallization using the hydrothermal method as shown in Table 1.…”
Section: Hydrothermal Methodsmentioning
confidence: 99%
“…In addition, the type of mineralization agent also has a great influence on the quality and growth rate of the crystal. Studies have shown that the use of acids, such as HCl, H 2 SO 4 , H 3 PO 4 , HNO 3 , and HCOOH, as mineralizers can reduce the crystal growth temperature to below 300 °C, thus allowing the use of relatively simpler autoclaves [51,52]. Tani et al [53] summarized the effect of mineralizers on ZrO 2 crystallization using the hydrothermal method as shown in Table 1.…”
Section: Hydrothermal Methodsmentioning
confidence: 99%
“…The well-established procedure involves alkali fusion from CFA followed by hydrothermal treatment to achieve a desired X-type zeolite structure [2]. For instance, the conversion of Indonesian zeolite into analcime (ANA) form was conducted under hot-water conditions [3] leading to zeolites with high crystallinity. Sandoval et al suggest that ANA can be manufactured from natural clinker [4].…”
Section: Introductionmentioning
confidence: 99%